Iradiasi Sinar ? pada Biak Tunas Kentang Hitam (Solanostemon rotundifolius) Efektif untuk Menghasilkan Mutan - Witjaksono, Witjaksono; Leksonowati, Aryani (JURNAL BIOLOGI INDONESIA, 2012)
Irradiation of ??ray at shoot culture of Kentang hitam (Solanostemon rotundifolius) is effective for mutant production. Kentang hitam is sterile and vegetatively propagated andtherefore its genetic diversity is narrow. Mutation is an alternative way to increase genetic heterogeneity. Irradiation of shoot cultures with different doses followed by culturing of the inoculum (leaf, petiole and internodes) from that irradiated culture on a regeneration medium MS containing 5 mg/l BA and 0.1 mg/l NAA has resulted in curvilinear respon of growth, morphogenesis and plant regeneration. The growth variables increase from 0 to 6 Gy and thendecrease to 25 and plateu or increase a little at 35 Gy and growth death wes observed at 50 Gy. Leaf and petiole inocula were more responsive than the internode. Respon of growth of shootregeneration of 50% were obtained at doses of 10-12.5 Gy. However higher level of doses, such as 25 Gy had also been effective for inducing mutant. Morphological and growth different were observed from growth in tissue culture to the field. Mutants were recovered, forexample, the one with early flowering.Keywords : Solanostemon rotundifolius, Irradiation, gammarays, cultur in vitro, mutan